Performance of blood glucose meters in compliance with current and future clinical ISO15197 accuracy criteria. (February 2014) - Pfützner, A.; Hengesbach, C.; Demircik, F.; Schipper, C.; Forst, T.; Musholt, P.B.
Abstract Since 2003, blood glucose meters for patient self testing are approved in Europe based on the accuracy performance criteria as defined by the ISO15197 guideline. A new draft ISO guideline is currently under regulatory review, which suggests more strict accuracy acceptance criteria, and which may not be entirely fulfilled by currently commercialized blood glucose meter systems. In order to investigate the compliance of BG*Star and iBG*Star and several other blood glucose meters with the new draft ISO guideline, we performed a post-hoc analysis of data obtained from a recently performed ISO-conforming clinical accuracy performance study. This study was performed with 106 patients, clinically presenting with blood glucose levels distributed over the entire measurement range and in line with the glucose distribution requirements as demanded by the guideline. The YSI 2300 STAT Plus analyzer (glucose oxidase) served as reference method. While all tested meters had been in a high degree of compliance with the current ISO criteria, performance was lower when analyzed in accordance with the new acceptance criteria (95% of readings have to be within ±15 mg/dL for values <100 mg/dL, and within ±15% for values ≥100 mg/dL). The following meters met the new criteria: Accu-Chek Aviva (95.5%/98.6%), BG*Star (98.5%/97.3%), iBG*Star (98.5%/97.3%), FreeStyle Freedom Lite (95.5%/96.6%), and OneTouch Ultra2 (95.5%/96.5%). One meter failed with low blood glucose values (Contour: 90.9%/95.9%). In conclusion, BG*Star and iBG*Star and several other branded meters met the new draft ISO15197 acceptance criteria, when tested in accordance with the instructions for use and with the ISO accuracy testing protocol in a clinical setting.